Experimental design of photo-Fenton process decolorization of Reactive Red 120 by using mathematical statistics models - Pucar Milidrag, Gordana; Bečelić Tomin, Milena; Rapajić, Sanja; Prica, Miljana; Kerkez, Đurđa; Dalmacija, Božo; Kulić Mandić, Aleksandra (Journal of Graphic Engineering and Design, 2018)
A statistical design of experiments was used to evaluate the potential use of clay catalyst (CuOFeB) during photo-Fenton process in which the concentration of hydrogen peroxide (H2O2), catalyst loading and pH values were selected as effective experimental factors in the process of dye decolorization. The photo-Fenton oxidation of Reactive Red 120 (RR120) has been investigated using a concentrating solar parabolic reactor with constant solar radiation of 950 W/m2 during summer period of the year. Under the optimal reaction conditions catalyst showed good catalytic activity in the processes with dye removal over 90%. Also, experiment confirmed that decolorization efficiency depends on the pH and concentration of H2O2 , wherein better results were achieved under lower pH values and higher concentration of H2O2.